If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 11) = (2x + -11) Reorder the terms: (11 + x) = (2x + -11) Remove parenthesis around (11 + x) 11 + x = (2x + -11) Reorder the terms: 11 + x = (-11 + 2x) Remove parenthesis around (-11 + 2x) 11 + x = -11 + 2x Solving 11 + x = -11 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 11 + x + -2x = -11 + 2x + -2x Combine like terms: x + -2x = -1x 11 + -1x = -11 + 2x + -2x Combine like terms: 2x + -2x = 0 11 + -1x = -11 + 0 11 + -1x = -11 Add '-11' to each side of the equation. 11 + -11 + -1x = -11 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = -11 + -11 -1x = -11 + -11 Combine like terms: -11 + -11 = -22 -1x = -22 Divide each side by '-1'. x = 22 Simplifying x = 22
| -9+2a-8a= | | 5x-(2x-4)=16 | | 5-x/6-2x-3/3=-1 | | 2n/5-3/11=73/55 | | (2x-11)=(x+11) | | 4x/9-2=2 | | 90+19m=432 | | 12(z+4)-3(z-1)=4(z-3)+4(z-2) | | 37n-180=375 | | 2p+-7=13+-8p | | 2x+1=4x-24 | | 6+7x=6x+8 | | 2x-5(x-4)=-3+2x-7 | | 52=-2(23-m)+4(m-4) | | sqrt(3)x+ay+1=0 | | 2x=27-5y | | 4(3x-9)-8=4(x-3)+8 | | 670=c+.35c | | 3x/2-10=6 | | 3x^2y^4-x^3-4y^3=2+4x | | 2z+iz=2+i | | 0.20x+8x=180 | | 0.045n=10.35 | | -1(d+6)= | | Y-6=-3(x+7) | | 5a+3b=2a+9b | | 2x/3=6/15 | | 60+12m=288 | | a*4=4 | | 5(3-(2-2x))+2x=2(6x+3)-1 | | 5(a-7)=29 | | 2x-4(x-4)=-7+3x-17 |